Enhancing Oral Production Skills Through TBL Implementation and Fostering Fellowship in an EFL Class at Seminario Menor de Medellin. (2020)
ABSTRACT: The following Action Research project tries to explore what the effects have to introduce TBL in a sixth grade, promoting students’ fellowship sense to foster speaking skills in an EFL class at a privet school in Medellin (Seminario Menor). In order to carry out this research, the process was based in observations, interviews and journals all that, collected during a period of a year. However, owing to the COVID-19, the unit implementation in this project had to be modified in terms of the cybernetic activities and strategies mediated by the virtuality. In order to promote students’ interaction and an increase their fellowship to foster their collaborative work and then obtain oral production skills development according with the student’s necessities.